PREVALENCE OF RHEUMATIC HEART DISEASE AMONG SCHOOL-GOING CHILDREN IN NORTHERN AND SOUTHERN REGIONS OF SARAWAK, MALAYSIA - Rudy Ngau, Ajeng; Md Mizanur, Rahman; Asri, Said; Mohamed Ameenudeen, Sultan; Greta Miranda Goh, Kim Choo; Muhammad Siddiq, Daud; Mohd Faiz, Gahamat (Malaysian Public Health Physician's Association, 2023)
Rheumatic Heart Disease (RHD) is a preventable chronic heart disease caused by rheumatic fever. RHD can result in complications and can even conclude in unexpected death at a young age. This study aimed to estimate the prevalence of RHD among the school-going age group in the Northern and Southern regions of Sarawak. This research was conducted as a cross-sectional study in Samarahan and Kuching of the Southern Region and Miri of the Northern Region of Sarawak. The study population comprised school-going children within the divisions. The data on sociodemographic characteristics were collected through a questionnaire. At the same time, echocardiographic parameters were collected through a portable echocardiographic device. Cardiologists confirmed the abnormal cardiac findings. The overall prevalence of RHD was 14 per 1000 persons or 1.4%. Borderline RHD prevalence was 9 per 1000 persons or 0.9%, while the Definite RHD prevalence was 5 per 1000 persons or 0.5 %. With the prevalence obtained, more attention should be given to preventing this silent disease.